2020
DOI: 10.1002/jcph.1725
|View full text |Cite
|
Sign up to set email alerts
|

Does “Birth” as an Event Impact Maturation Trajectory of Renal Clearance via Glomerular Filtration? Reexamining Data in Preterm and Full‐Term Neonates by Avoiding the Creatinine Bias

Abstract: Glomerular filtration rate (GFR) is an important measure of renal function. Various models for its maturation have recently been compared; however, these have used markers, which are subject to different renal elimination processes. Inulin clearance data (a purer probe of GFR) collected from the literature were used to determine age-related changes in GFR aspects of renal drug excretion in pediatrics. An ontogeny model was derived using a best-fit model with various combinations of covariates such as postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 60 publications
(122 reference statements)
0
26
0
2
Order By: Relevance
“…This is commonly accounted for in PK models using either PNA and/or PMA as covariates on CL [ 14 , 18 , 25 ]. However, several studies have suggested that PMA is insufficient to describe postnatal GFR maturation as it ignores the impact of birth on GFR [ 18 , 26 ]. Indeed, Salem et al showed that in a group of neonates with the same PMA values, neonates with a higher PNA have higher GFR values as compared with more mature cases at birth, but with a lower PNA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is commonly accounted for in PK models using either PNA and/or PMA as covariates on CL [ 14 , 18 , 25 ]. However, several studies have suggested that PMA is insufficient to describe postnatal GFR maturation as it ignores the impact of birth on GFR [ 18 , 26 ]. Indeed, Salem et al showed that in a group of neonates with the same PMA values, neonates with a higher PNA have higher GFR values as compared with more mature cases at birth, but with a lower PNA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have suggested that PMA is insufficient to describe postnatal GFR maturation as it ignores the impact of birth on GFR [ 18 , 26 ]. Indeed, Salem et al showed that in a group of neonates with the same PMA values, neonates with a higher PNA have higher GFR values as compared with more mature cases at birth, but with a lower PNA [ 26 ]. In other words, postnatal GFR maturation is best described using PNA rather than PMA.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, the combination of gestational age or birthweight with postnatal age, and not PMA, were the best predictors of PK in a large heterogeneous group of preterm neonates. When it comes to renal function, the impact of birth on the maturation of glomerular filtration rate has recently been clearly shown by Salem et al [ 12 ].…”
mentioning
confidence: 99%
“…The authors reported that the time to half the adult value of the glomerular filtration rate occurred at 47.7 weeks of post–menstrual age, suggesting that maturation in renal function will be an important predictor of clearance in neonates and infants 24 . Another study developed an ontogeny function based on postnatal age, gestational age at birth, and body weight and identified birth as an important determinant of glomerular filtration rate for pediatric patients fewer than 105 weeks post–menstrual age 25 . Another important consideration is that body size‐related developmental changes in organ size, composition, and perfusion occur disproportionately with age.…”
Section: Drug‐related Considerationsmentioning
confidence: 99%